PEREMPUAN DUNIA KETIGA DALAM ANTOLOGI CERITA PENDEK “KETIKA SAATNYA” - Ramis Rauf; Afriani Ulya (Kantor Bahasa Provinsi Gorontalo, 2021)
The aim of this study was to reveal the phenomenon of socio-cultural facts of women as subalterns in the anthology of the short story